Placental Oxidative Status throughout Normal Gestation in Women with Uncomplicated Pregnancies - Basu, Jayasri (Obstet Gynecol Int, 2015)
The effects of gestational age on placental oxidative balance throughout gestation were investigated in women with uncomplicated pregnancies. Placental tissues were obtained from normal pregnant women who delivered at term or underwent elective pregnancy termination at 6 to 23 + 6 weeks of pregnancy. Placental tissues were analyzed for total antioxidant capacity (TAC) and lipid peroxide (malondialdehyde, MDA) levels using commercially available kits. Two hundred and one placental tissues were analyzed and the mean ± SD MDA (pmol/mg tissue) and TAC (µmol Trolox equivalent/mg tissue) levels for first, second, and third trimester groups were 277.01 ± 204.66, 202.66 ± 185.05, and 176.97 ± 141.61, P < 0.004 and 498.62 ± 400.74, 454.90 ± 374.44, and 912.19 ± 586.21, P < 0.0001 by ANOVA, respectively. Our data reflects an increased oxidative stress in the placenta in the early phase of normal pregnancy. As pregnancy progressed, placental antioxidant protective mechanisms increased and lipid peroxidation markers decreased resulting in diminution in oxidative stress. Our findings provide a biochemical support to the concept of a hypoxic environment in early pregnancy. A decrease in placental oxidative stress in the second and third trimesters appears to be a physiological phenomenon of normal pregnancy. Deviations from this physiological phenomenon may result in placental-mediated disorders.